2011
DOI: 10.1242/jeb.057620
|View full text |Cite
|
Sign up to set email alerts
|

Migration- and exercise-induced changes to flight muscle size in migratory birds and association withIGF1andmyostatinmRNA expression

Abstract: SUMMARYSeasonal adjustments to muscle size in migratory birds may result from preparatory physiological changes or responses to changed workloads. The mechanisms controlling these changes in size are poorly understood. We investigated some potential mediators of flight muscle size (myostatin and insulin-like growth factor, IGF1) in pectoralis muscles of wild wintering or migrating white-throated sparrows (Zonotrichia albicollis), captive white-throated sparrows that were photoperiod manipulated to be in a 'win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 74 publications
3
39
2
2
Order By: Relevance
“…The reduced pectoralis myostatin protein levels with increased energy demands for both training groups is generally consistent with trends in myostatin expression during winter acclimatization in small birds, including house sparrows (Swanson et al, 2009. However, reduced pectoralis myostatin mRNA and TLL expression has not been previously documented during migration, although pectoralis myostatin protein levels may decrease in the migratory state (Price et al, 2011;King et al, 2015).…”
Section: Among Birds Tufted Duckssupporting
confidence: 79%
See 2 more Smart Citations
“…The reduced pectoralis myostatin protein levels with increased energy demands for both training groups is generally consistent with trends in myostatin expression during winter acclimatization in small birds, including house sparrows (Swanson et al, 2009. However, reduced pectoralis myostatin mRNA and TLL expression has not been previously documented during migration, although pectoralis myostatin protein levels may decrease in the migratory state (Price et al, 2011;King et al, 2015).…”
Section: Among Birds Tufted Duckssupporting
confidence: 79%
“…Myostatin is secreted as an inactive latent form that requires cleavage by metalloproteinases, including the tolloid-like proteins TLL-1 and TLL-2, to produce the active C-terminal dimer (Huet et al, 2001;Wolfman et al, 2003). Several studies have examined variation in expression of myostatin and the TLL proteins in birds during periods (migration and winter acclimatization) that cause variation in muscle mass (Swanson et al, 2009Price et al, 2011;King et al, 2015). These studies offer variable support for a role for myostatin in regulating flexible muscle masses throughout the annual cycle in birds, with some finding negative relationships between expression of myostatin and the TLLs and M pec (Swanson et al, 2009), others finding no or positive relationships (Price et al, 2011) and still others finding different trends for mRNA and protein levels King et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guernec et al, 2003), but their role in seasonal regulation of avian adult muscle size is unclear. Swanson et al (2009Swanson et al ( , 2014b found that increases in pectoralis size of wintering passerine birds were associated with decreased expression of MSTN or its metalloproteinase activators (TLL-1, TLL-2), but increases in flight muscle size of photo-stimulated white-throated sparrows (Zonotrichia albicollis) were conflictingly accompanied by increased expression of both IGF1 and MSTN (Price et al, 2011). Although IGF1 expression was not detected in our dataset, MSTN expression did not differ significantly among either temperature or photoperiod treatments.…”
Section: Transcriptomic Signatures Of Muscle Growthmentioning
confidence: 55%
“…Captivity was expected to have weak but negative effects on these traits because: (1) birds would be able to exercise little in cages [and thus experience atrophy due to disuse (Portugal et al, 2009;Price et al, 2011)], and (2) chronically elevated CORT tends to degrade muscle in domesticated game birds (Dong et al, 2007;Hull et al, 2007) and wild songbirds (Awerman and Romero, 2010; Busch et al, 2008;Gray et al, 1990). As our study was not designed to determine how captivity altered muscle growth and viability in sparrows on the molecular level, we can only speculate as to why house sparrow physical performance improved with captivity duration.…”
Section: Captivity Effects On Flight Muscle and Performancementioning
confidence: 99%